Kecerdasan Buatan dalam Konsep Enframing oleh Heidegger Pada Masyarakat Modern - Husnita, Sri Rezeky Indiani; Sitorus, Fitzerald Kennedy (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This article examines Martin Heidegger’s philosophy of technology, particularly the concept of enframing (Ge-Stell), in relation to artificial intelligence (AI) in the digital era. Heidegger rejects the notion that technology is neutral and emphasizes that it shapes how humans understand reality through a logic of efficiency and control. This study employs a qualitative method through literature review of Heidegger’s works and contemporary sources on AI. The findings show that AI not only mediates but also constructs reality, blurring the boundary between the real and the artificial. Within the framework of enframing, humans and nature are reduced to resources, sidelining existential values. This article conclude that Heidegger does not reject technology but calls for reflective awareness of its hidden logic and openness to more authentic modes of revealing, so that humanity does not become trapped in a world entirely shaped by technological reasoning.